2015
DOI: 10.3846/16484142.2015.1020872
|View full text |Cite
|
Sign up to set email alerts
|

Verhead Crane Anti-Swing System Based on the Pontryagin’s Maximum Principle

Abstract: Overhead cranes are widely used at industrial enterprises for transportation of materials and products. They are successfully adaptable to technological processes used at an enterprise and their exploitation is inexpensive; in addition, the price of cranes is relatively low. However, extension of requirements set for technological processes results in shortened time for transportation and stiffened requirements for accuracy of cargo delivery and cargo safety. In the attempts to satisfy the latter requirements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Simulation model of the overhead crane was developed using MATLAB/Simulink software [21]. Previous research works [22] showed that significant load swing occurs during transportation by the overhead crane.…”
Section: Model and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation model of the overhead crane was developed using MATLAB/Simulink software [21]. Previous research works [22] showed that significant load swing occurs during transportation by the overhead crane.…”
Section: Model and Simulationmentioning
confidence: 99%
“…During the creation of the mathematical model, experience of industrial enterprise Vilniaus kranai AB was evaluated claiming that rope angular deviation from the vertical does not exceed 5 degrees. Obtained after appropriate processing in accordance with techniques presented in [23] equations and used coordinates are presented in [21]. Modeling of the mechanical system was carried out with the following parameters (data obtained from the experiments carried out at Vilniaus kranai AB): standard gravity g=9.81m/s 2 , load mass M=1000kg, trolley mass M x =5000kg, mass of the trolley and the bridge M y =10000kg, damping coefficient at the rope attachment point H 2 =1Nms/rad, rope damping coefficient H 1 =1000Ns/m, initial rope tension stiffness C 1 =1716000N/m, damping coefficient of the trolley along axis X H x =1000Ns/m, damping of the crane along axis Y H y =2000Ns/m.…”
Section: Model and Simulationmentioning
confidence: 99%
“…However, an experimental way cannot be the only technique for investigating all possible combinations of operating parameters due to high costs and time spent for determining the optimal values. Mathematical modeling of a physical system employing numerical methods has become an effective alternative (Bogdevičius and Vitkūnas 2016;Andrikaitis and Fedaravičius 2014;Najafi and Ahmadzadeh 2014;Skrickij et al 2016;Spruogis et al 2015;Dyakov and Prentkovskis 2008;Moezi et al 2015;Bogdevičius et al 2015;Dönmez Demir et al 2015;Khatir et al 2014;Ahmadi et al 2015;Zhang et al 2015;Simonović 2015;Allali et al 2015). The paper is aimed on proposing mathematical model for the pneumatic damping system.…”
Section: Introductionmentioning
confidence: 96%
“…The solution to such a global problem can be found by methods of variations, including using the Pontryagin maximum principle, providing that the system of equations 5 is differentiated by variables x 1 , x 2 , and that the corresponding Hamiltonian should reach a maximum at the range t o ... T [11]. This problem, for the route with a constant resistance of driving, has been solved before [14].…”
Section: Methods Of Solutionmentioning
confidence: 99%